Thinking with Marx Today, Volume 2 : "Man?" - Sève, Lucien, (Historical Materialism Book Series ;, 2026)
Instead of abstract "man," Marx argued that there is an ensemble of societal relations that underpins social formations of various kinds as well as a variety of forms of individuality. In this second volume of Thinking with Marx Today, Lucien Sève presents what he calls Marx's revolution in anthropology. He deftly analyzes the philosophical preconditions and the fundamental concepts of this anthropology. This is followed by critiques of Nietzsche, Heidegger, and contemporary primatology coupled with borrowings from Freud, Politzer, Vygotsky, and contemporary literature on biography. Sève's aim is nothing less than to outline a science of human individuality.